2019
DOI: 10.1093/cid/ciz380
|View full text |Cite
|
Sign up to set email alerts
|

Subtherapeutic Rifampicin Concentration Is Associated With Unfavorable Tuberculosis Treatment Outcomes

Abstract: Background The relationships between first-line drug concentrations and clinically important outcomes among patients with tuberculosis (TB) remain poorly understood. Methods We enrolled a prospective cohort of patients with new pulmonary TB receiving thrice-weekly treatment in India. The maximum plasma concentration of each drug was determined at months 1 and 5 using blood samples drawn 2 hours postdose. Subtherapeutic cutoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Individualized dosing is crucial to ensure optimal rifampicin exposure, since treatment failure, resistance development, and relapse of TB disease have been linked to suboptimal rifampicin plasma concentrations (Pasipanodya et al, 2013;Alsultan and Peloquin, 2014;Ramachandran et al, 2019). To prevent prolonged treatment, which increases the patient's risk for adverse events and treatment costs, it is critical to use approaches ensuring that adequate drug exposure is achieved in every patient, which can be accomplished through MIPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individualized dosing is crucial to ensure optimal rifampicin exposure, since treatment failure, resistance development, and relapse of TB disease have been linked to suboptimal rifampicin plasma concentrations (Pasipanodya et al, 2013;Alsultan and Peloquin, 2014;Ramachandran et al, 2019). To prevent prolonged treatment, which increases the patient's risk for adverse events and treatment costs, it is critical to use approaches ensuring that adequate drug exposure is achieved in every patient, which can be accomplished through MIPD.…”
Section: Discussionmentioning
confidence: 99%
“…Rifampicin is one of the core-drugs in the first-line treatment of drug-susceptible tuberculosis (TB) (WHO, 2017). With the currently recommended dosage of 10 mg/kg once daily (WHO, 2017), a substantial amount of patients do not reach sufficient drug exposure, which has been shown to result in treatment failure, development of drug resistance, and disease relapse (Pasipanodya et al, 2013;Alsultan and Peloquin, 2014;Ramachandran et al, 2019). Therefore, higher doses of rifampicin have been studied and were shown to lead to higher efficacy than the current recommended dosage (Svensson et al, 2018b), while still being safe (Boeree et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The geographic location of the included studies was; six from Africa, [25][26][27][28][29][30] one from Europe, 31 two from Latin America, 32,33 and the remaining three from Asia. [34][35][36] The majority of the studies were observational prospective in design. Only two of the studies included in this review were randomized clinical trials as shown in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In all studies, some participants had comorbid conditions; either HIV or diabetes mellitus. 29,[33][34][35][36] The PRISMA Flow diagram is shown in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation